"The Effect of Physical Work Environment on the Job Satisfaction of Nurses in the Rural Health Care Settings of Punjab, Pakistan" - Iqra Nawaz, Ashfaq Ahmed Maan, Izhar Ahmad Khan, Babar Shahbaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Pakistan faces a severe shortage of nurses because of high turnover rates. Job dissatisfaction is one of the leading causes of turnover intentions. An excellent physical environment in the workplace setting can play a positive role in enhancing the satisfaction level among the employees. The present study investigated the effect of the physical work environment on the job satisfaction level of the nurses working in rural health settings. Data were collected from 452 randomly selected nurses from the rural health care settings of the Punjab province. The quantitative survey design was used to collect data. The five-point Likert scale was used to collect the data on the conditions of physical work environment and job satisfaction of the nurses. A structured questionnaire was developed. The mean score and standard deviations were used to describe the data collected. The study's findings suggest adequate levels of job satisfaction and a comfortable physical environment among nurses working in Punjab's rural health care settings. The physical environment at the workplace is responsible for 43 % variation in the job satisfaction level of the nurses. The physical environment at the workplace is the strongest predictor of the job satisfaction level among nurses. By improving the physical work environment of the workplace, the retention rate of nurses can be improved.